2022
DOI: 10.1038/s41408-022-00677-7
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes in patients with relapsed/refractory FLT3-mutated acute myeloid leukemia treated with gilteritinib who received prior midostaurin or sorafenib

Abstract: The fms-like tyrosine kinase 3 (FLT3) inhibitor gilteritinib is indicated for relapsed or refractory (R/R) FLT3-mutated acute myeloid leukemia (AML), based on its observed superior response and survival outcomes compared with salvage chemotherapy (SC). Frontline use of FLT3 tyrosine kinase inhibitors (TKIs) midostaurin and sorafenib may contribute to cross-resistance to single-agent gilteritinib in the R/R AML setting but has not been well characterized. To clarify the potential clinical impact of prior TKI us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 37 publications
(71 reference statements)
0
24
0
1
Order By: Relevance
“…Therefore, dual Axl and FLT3-ITD inhibitors have an advantage in targeting FLT3-ITD selective inhibitor-resistant AML cells. In support of this, there is a report showing that sorafenib-resistant FLT3-ITD patients respond to gilteritinib [ 49 ]. However, gilteritinib still exhibits transient effects in FLT3-ITD AML patients.…”
Section: Discussionmentioning
confidence: 80%
“…Therefore, dual Axl and FLT3-ITD inhibitors have an advantage in targeting FLT3-ITD selective inhibitor-resistant AML cells. In support of this, there is a report showing that sorafenib-resistant FLT3-ITD patients respond to gilteritinib [ 49 ]. However, gilteritinib still exhibits transient effects in FLT3-ITD AML patients.…”
Section: Discussionmentioning
confidence: 80%
“…Although SHP2 inhibitors are only in early phase trials, the FLT3 inhibitor Gilteritinib is used clinically for the treatment of FLT3-ITD + AML (50, 51). MOLM13 and MV4-11 express FLT3-ITD, and our results indicate that INPPL1, MAP4K5, and LZTR1 act downstream of this fusion-RTK receptor.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have suggested that prior exposure to FLT3 inhibitors may increase the clone transformation and induce resistance [48][49][50]. Alvarado et al found that secondary FLT3-TKD mutations emerged after treatment with FLT3 inhibitors in FLT3-ITD mut AML and may be associated with resistance and poor prognosis [50].…”
Section: Discussionmentioning
confidence: 99%